The Reflux Technique for Safe Delivery of Obsidio - Mohammed, Alaaeldeen; Sarkar, Debkumar; Cornelis, Francois H. (Journal of Clinical Interventional Radiology ISVIR, 2025)
Obsidio, a polyethylene glycol-based hydrogel conformable embolic agent, is a 510(k) cleared device with shear-thinning technology, enabling precise and durable embolization. This case describes its use in an 88-year-old patient undergoing preoperative embolization for a metastatic deposit in the left acetabulum from renal cell carcinoma. While distal embolization was initially achieved with ethylene-vinyl alcohol copolymer, persistent proximal feeders required additional embolization. A reflux technique was employed, allowing controlled proximal cast formation while minimizing distal migration. Comprehensive tumor vascular occlusion was achieved, enabling surgery with minimal blood loss. This case demonstrates Obsidio's versatility and highlights the reflux technique's role in optimizing outcomes for complex embolization procedures.
Keywords: Obsidio; embolization; cancer